2018
DOI: 10.19106/jmedscie/005004201814
|View full text |Cite
|
Sign up to set email alerts
|

The role of isoflavon in reducing blood glucose levels

Abstract: Plants provide excellent sources of medicinal compounds. Over 5000 flavonoids have been isolated and identified from plant sources. Flavonoids are polyphenolic compounds mainly recognized as pigments which produce the colors found in flowers, fruit and leaves. Dietary polyphenols are commonly found in plants and are abundant in fruit, vegetables, chocolate, and nuts. These polyphenols also found in beverages including tea, coffee, wine, and soy milk. Flavonoids are known to lower glucose levels, decrease chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…MDA levels were reduced in several preclinical studies [16,19,20,23,34,[36][37][38][39][41][42][43][45][46][47]51,56]. Interestingly, similar findings were observed in clinical studies, as shown by a decrease in MDA levels [26,30,53,66].…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…MDA levels were reduced in several preclinical studies [16,19,20,23,34,[36][37][38][39][41][42][43][45][46][47]51,56]. Interestingly, similar findings were observed in clinical studies, as shown by a decrease in MDA levels [26,30,53,66].…”
Section: Discussionsupporting
confidence: 58%
“…Treating STZ-induced diabetic Wistar rats with pomegranate juice at doses of 100 mg/kg and 300 mg/kg for four weeks resulted in increased GSH (56.25 ± 1.90 nM/mg and 66.51 ± 1.82 nM/mg compared to 34.67 ± 2.76 nM/mg, p < 0.05), CAT (47.14 ± 1.65 U/mg and 66.36 ± 1.99 U/mg compared to 16.47 ± 0.79 U/mg, p < 0.05), and SOD levels (165.3 ± 3.25 U/mg, 237.9 ± 19.72 U/mg compared to 45.62 ± 6.10 U/mg, p < 0.05) and decreased levels of TBARS (1.247 ± 0.02 µM/mg and 0.80 ± 0.02 µM/mg in respective dosage compared to untreated group 2.23 ± 0.04 µM/mg, p < 0.05) [24]. Some contrasting findings were dose-dependent as Praseytastuti et al [51] revealed that STZ-induced diabetic Sprague Dawley rats for four weeks of pomegranate juice only 2 mL/200 g of PJ could significantly decrease MDA levels while 1 and 4 mL/200 g showed no difference in MDA levels (post-treatment, 0.69 ± 0.22 µmol/L compared to baseline 2.02 ± 1.68 µmol/L, p > 0.05 at 1 mL/200g). Moreover, at 2 mL/200 g (0.68 ± 0.38 µmol/L compared to 2.02 ± 1.68 µmol/L, p < 0.05 at 2 mL/200 g) and 0.85 ± 0.12 µmol/L compared to 3.16 ± 2.09 µmol/L at a dose of 4 mL/200 g. This is partially supported by more recent evidence, as a study by Abdulhadi et al [53] showed that intraperitoneal injection of punicalagin at 1 mg/kg for 15 days in STZ-induced diabetic Wistar rats showed a significant decrease in MDA formation in the pancreas (p < 0.001).…”
Section: The Effect Of Pomegranate and Its Derivatives On Markers Of ...mentioning
confidence: 91%
See 1 more Smart Citation
“…Isoflavones can reduce blood glucose levels. Supplementation with isoflavones is known to suppress gluconeogenic enzyme activity and reduce β-oxidation of fatty acids and lipid accumulation (14,15). The increasing cases of NCDs (cardiovascular disease, T2DM, and stroke) in Indonesia are expected to increase the burden on society and the government.…”
Section: Introductionmentioning
confidence: 99%